Reporting the Road to Brexit International Media and the EU Referendum 2016 (Springer International Publishing, 2018)
This edited collection brings together leading international scholars to explore the connection between Brexit and the media. The referendum and the activism on both sides of the campaign have been of significant interest to the media in the UK and around the world. How these factors have been represented in the media and the role of the media in constructing the referendum narrative are central to assisting the development in our understanding of how UK and global democracy is being manifested in contemporary times. This book explores these topics through presenting a wide range of perspectives from research conducted by leading international scholars, and concludes with an assessment of the potential democratic and international implications for the future. By grappling with a highly important and controversial topic in a comparative and varied way, the volume contributes to theoretical debates about the nature and role of the media in complex social, political and cultural contexts.